Effectiveness of welfare development scheme on quality of life to rural poor community in Malaysia - Abdul Aziz, Mohd Nizam (2014)
Malaysia is committed to achieve a developed country in the year of 2020. One of the significance progresses towards the vision and mission is eradicate poverty population. SPKR programme is one of the main poverty eradication programmes in Malaysia. Main target of SPKR is to achieve 0.5 percents level of poverty in the year of 2005. However, in year 2010, the poverty incidence in Malaysia still in 2.9%. This study is to investigate did the percentage have been achieved by year 2005 and to investigate the current percentage of poverty population in Malaysia. The main finding for this research is to investigate and determine the successful of the programme to the poor community. Meanwhile the specific objective for this research conclude to identify the respondents’ socio-demographic profiles, to determine the relationship between socio-demographic factors and level of generating income, to determine SPKR participant’s satisfactions on changes of quality of life (in the context of economy and social) after they attended the programme and to identify the factors that influences the effectiveness of SPKR programme on the changes of participants’ quality of life. This research is using quantitative framework. A total five which reported have higher poverty populations in Peninsular Malaysia were selected. The states are from East Coast region (Kelantan and Terengganu) and North Coast region (Perlis, Kedah, and Perak). Those states are the main subject chose by Ministry of Rural And Regional Development Malaysia in eradicating poverty population. In this survey, questionnaire has been used to get raw data from the SPKR programme participants (N=1122). The participants was categorized as standard poverty population which their household income are below RM700 per month. The respondents were selected by purposive random sampling in the survey. Respondent also selected from the poverty programmes which focused on capacity building of the target group. The capacity building includes income increment, human development, rural community economy, and community development. This study was based on primary data, while the secondary data is to strengthen the facts and as supplementary of this research. In this study, the data conclude both qualitative and quantitative output. In this study, structured questionnaires with open and close-ended questions were the main instrument used in collecting data for this research. This research was based on primary data that collected through interview or face-to-face with the respondents. There were four main statistical techniques were used in this research. All those techniques were chosen due to fulfil the objectives of this research. Factor analysis, chi-square, descriptive analysis and logistic regression were applied in analyzing method for this study. SPSS was a medium of analyzing data in this study. Regarding to the analysis, more than three-quarter of the respondents (87.4 percent) strongly agreed that their quality of life getting better after participate SPKR programme. After participated SPKR programme, majority of respondents strongly satisfy (54.6 percent) and satisfy (37.8 per cent) with their income level increments (mean = 4.48). This is mean that the respondents able to enhance their quality of life thus exit from poverty line. 58.5 per cent respondents have agreed in the responsibility done by SPKR in enhancing poverty community life (mean = 4.29). Majority of respondents agree (68.8 per cent) and strongly agree (22.6 percent) in their proactive improving their living standards. Most of the respondents (43.6 percent) response that they agreed of the time of visits by implementing agencies to monitor them from time to time. Respondents were agreed (52.2 percent) to appoint that the implemented poverty programme was fulfil respondents’ needs (mean = 2.54). 64.3 per cent of respondents agreed and 30 per cent has strongly agreed that local residents who are given a support of to ensure the successful of the programme (mean = 4.23). There were significant relationship test between social-demographic factors and monthly household income which include state of origin (.014), marital status (.000), education (.000), gender (.000) and age (.000). There are significant at 0.05 and 0.10 level respectively. There were four factors detected on respondents’ perceptions towards their Quality of life (QoL) and they were the level of importance, implementing agency, living and residency, and communication application. As conclusion, this study can be a reference to Malaysia and all institutions which are related in eradicating poverty programmes in Malaysia. The government of Malaysia should take more actions and give these programmes priority for all related institutions. This study would be invigorated to all government agencies, policy maker, researchers, and all institutions through publication of this thesis. This kind of sharing information is very useful and important to government and all related institutions which involved in the programmes in Malaysia. Hopefully this study can be used for them to plan and executing eradication poverty programmes for increment of poor community quality of life especially in rural area, while bring them exit path from poverty life.